The response of maize production in Kenya to economic incentives - Onono, Perez Ayieko; Wawire, Nelson W.H.; Ombuki, Charles (My University, 2013)
Agricultural development policy in Kenya has emphasised the use of incentives towards increased production and therefore self-sufficiency in maize which is a basic staple for most households. The channels used to provide incentives to maize farmers over the years include setting higher producer prices; subsidisation of inputs; provision of agricultural credit, research and extension services; construction and maintenance of roads, development of irrigation and water systems; legislative, institutional and macroeconomic reforms. Despite these efforts outputof maize has remained below domestic requirements in most years and the country continues to rely on imports to meet the deficits. Studies have assessed the responsiveness of maize to output price and reported inelastic responses and have recommended policies targeting non-price incentives to complement prices for the required increased production of maize. The studies, however, did not analyse the influence of the non-price incentives on the production of the crop. The findings of those studies are therefore deficient in explaining the relative importance of different non-price incentives and how they complement prices in influencing maize production in Kenya. This study investigated the response of maize production to both price and non-price incentives. The aim of this study was to ascertain the relative importance of non-price factors in influencing production of the crops as well as complementarity between price and non-price incentives. The findings show that maize production responds positively to its output price, development expenditures in agriculture, maize sales to marketing boards, growth in per capita GDP, liberalisation and governance reforms. However, maize production responds negatively to fertiliser price and unfavourable weather conditions. The response of maize output to its price is lower with rising inflation and grain market liberalisation. Keywords: Maize production response, Price Incentives, Non-price incentives